Norman Street : poverty and politics in an urban neighborhood - Susser, Ida. (New York ; Oxford : Oxford University Press, 2012)
Based on a three-year study conducted in Brooklyn's Greenpoint/Williamsburg section, this book is an in-depth, detailed description of life in a multi-ethnic working class neighborhood during New York City's fiscal crisis of 1975-1978. Now updated with a new introduction to address the changes and events of the thirty years since the book's original publication, its lessons still resonate in the impact of political and economic changes on everyday lives.
Previous ed.: 1982.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Keywords: Municipal services -- New York (State) -- New York; Finance, Public -- New York (State) -- New York; Brooklyn (New York, N.Y.) -- Economic conditions; Brooklyn (New York, N.Y.) -- Social conditions